2015
DOI: 10.1155/2015/789038
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma Detection Rates Decline with Increasing Procedural Hours in an Endoscopist’s Workload

Abstract: The number of hours devoted to endoscopies before the index colonoscopy was inversely associated with AD rate, with decreased performance possibly as early as within 3 h. This metric should be confirmed in future studies and considered when optimizing scheduling practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Our results differ from other studies which found no association between fatigue and adenoma detection. However, many of these negative studies had smaller sample sizes (400–4,000 colonoscopies), [7, 8, 1012, 14] which may have limited their power to identify a difference. Another possibility for the discrepancy is differences in physician payment and practice style between settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our results differ from other studies which found no association between fatigue and adenoma detection. However, many of these negative studies had smaller sample sizes (400–4,000 colonoscopies), [7, 8, 1012, 14] which may have limited their power to identify a difference. Another possibility for the discrepancy is differences in physician payment and practice style between settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, a diagnosis based on endoscopic findings requires training ( Sugano et al, 2015 , Watanabe et al, 2013 ), is time-consuming and subjective, and may result in false-positive and false-negative results depending on the skill of the endoscopist. Further, fatigue may adversely affect the diagnostic yield of this investigation as shown in a previous report, wherein the adenoma detection rates via colonoscopy declined with increasing procedural hours ( Almadi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 88%
“…21 Furthermore, it has been reported that adenoma detection rates decrease with increasing time devoted to endoscopies because of the fatigue, supporting the idea that computer-aided detection might provide more reliable results. 22 Convolutional neural networks (CNNs) are one of the most popular network architectures of deep learning for images. 11,23 Recent studies showed a promising role for CNNs for the detection or classification of CP during colonoscopy.…”
Section: Introductionmentioning
confidence: 99%